2020
DOI: 10.3390/ijms21134664
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Genome Assembly of Fennel (Foeniculum vulgare) Reveals Two Different atp6 Gene Sequences in Cytoplasmic Male Sterile Accessions

Abstract: Cytoplasmic male sterility (CMS) has always aroused interest among researchers and breeders, being a valuable resource widely exploited not only to breed F1 hybrid varieties but also to investigate genes that control stamen and pollen development. With the aim of identifying candidate genes for CMS in fennel, we adopted an effective strategy relying on the comparison between mitochondrial genomes (mtDNA) of both fertile and sterile genotypes. mtDNA raw reads derived from a CMS genotype were assembled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The newly obtained line (strain CMS) will then be used as a mother plant (or seed plant) and crossed with strain P for F1 hybrid production, while strain M will be used to maintain strain CMS. By crossing highly dissimilar strains P and CMS, the resulting offspring are expected to exhibit a high level of heterozygosity, maximizing heterotic vigor [7,9,10]. Following F1 hybrid development, the registration process of the new plant variety is subject to compliance with rigorous and specific requirements concerning distinctness (D), uniformity (U) and stability (S).…”
Section: Introductionmentioning
confidence: 99%
“…The newly obtained line (strain CMS) will then be used as a mother plant (or seed plant) and crossed with strain P for F1 hybrid production, while strain M will be used to maintain strain CMS. By crossing highly dissimilar strains P and CMS, the resulting offspring are expected to exhibit a high level of heterozygosity, maximizing heterotic vigor [7,9,10]. Following F1 hybrid development, the registration process of the new plant variety is subject to compliance with rigorous and specific requirements concerning distinctness (D), uniformity (U) and stability (S).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, MS seems to be more common within the Apiaceae family. Cytoplasmic male sterility (CMS), a maternally inherited trait that is often associated with single-gene mutations in the mitochondrial genome [ 39 ], has been reported in Daucus carota (for a review see [ 40 ]) but also in Foeniculum vulgare [ 41 ], Apium graveolens [ 42 ] and Pastinaca sativa [ 43 ]. In Apium graveolens , the discovery of CMS genotypes has been reported since the 1980s, and few F1 hybrids available on the market for celery and celeriac ( A. graveolens var.…”
Section: Plant Reproductive Strategies and Breeding Schemes In The Apiaceae Familymentioning
confidence: 99%
“…Due to the economic interest behind this trait, the mechanisms and origin of male sterility are often contained by the breeding companies, and reports on CMS sources are elusive. Only in few cases are the genetics underlying the lack of pollen elucidated [ 40 , 41 ]. It is well established that one of the most effective strategies to identify the genes responsible for CMS is the comparison between mitochondrial genomes (mtDNA) of fertile and sterile genotypes to identify differences in terms of sequences and/or structure organization.…”
Section: Plant Reproductive Strategies and Breeding Schemes In The Apiaceae Familymentioning
confidence: 99%
See 1 more Smart Citation
“…RAFTIN gene in rice and wheat (Wang et al, 2003), OsDEX1, a Ca 2+ binding protein in rice (Yu et al, 2016) also been reported to associate with male sterility. Palumbo et al, (2020) reported role of two atp6 gene sequences for CMS in Fennel (Foeniculum vulgare) by mitochondrial genome assembly of male sterile and fertile accessions. Similarly, the mechanism of abortion in CMS was studied and reported by transcriptome analysis in CMS tobacco and fertile lines .…”
Section: Mitochondria a Powerful Organelle For Male Sterilitymentioning
confidence: 99%